2020
DOI: 10.4102/ajod.v9i0.628
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the status of resilience amongst adults with blindness in Addis Ababa

Abstract: Background Living with blindness for anyone, whether educated or uneducated, rich or poor, with adequate support or without it is seriously limiting. The quality of life of people with blindness is significantly influenced by the level of resilience they possess. The status of resilience of adults with blindness living in Addis Ababa is not known. Objectives Against this backdrop, this study was designed to explore the level of resilience of Adults living with blindness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In extreme cases, the victims will experience paranoia which may develop chronic disabilities such as agoraphobia [20], [23]. In addition, trauma impact can be seen in low self-esteem, high levels of anxiety, depression, drugs abuse, being an alcoholic, sexual risk taking, lack of intimacy, PTSD, and suicidal behavior [5], [6], [7], [15], [18], [19], [20], [21], [22]. Other studies have mentioned long-term problems of male victims including sexual dysfunction and difficulty in relationships [20], [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In extreme cases, the victims will experience paranoia which may develop chronic disabilities such as agoraphobia [20], [23]. In addition, trauma impact can be seen in low self-esteem, high levels of anxiety, depression, drugs abuse, being an alcoholic, sexual risk taking, lack of intimacy, PTSD, and suicidal behavior [5], [6], [7], [15], [18], [19], [20], [21], [22]. Other studies have mentioned long-term problems of male victims including sexual dysfunction and difficulty in relationships [20], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning sexual assault occurred in the visually impaired have found physical, psychological and social problems as some of the consequences of these events. A study from Zegeye in Addis Ababa found that blind women experiencing sexual assault have physiological consequences including lack of sleep, nightmares, headaches and poor appetite [5]. Psychological consequences of sexual harassment which arise include irritability, fear, phobias, depression, and risk of suicide [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being blind is seriously challenging for anyone (Genet, Kumar & Sulphey 2021;Zegeye 2020). This would be more so for blind female university students, as they are expected to handle the challenges of blindness, being female, and the demands of tertiary education in parallel.…”
Section: Introductionmentioning
confidence: 99%